Intention of having a second child among infertile and fertile women attending outpatient gynecology clinics in three major cities in China: a cross-sectional study. Issue 4 (25th September 2018) - Lau, Bobo Hi-Po; Huo, Ran; Wang, Kun; Shi, Li; Li, Rong; Mu, Sha; Peng, Hongmei; Wang, Yu; Chen, Xiujuan; Ng, Ernest Hung-Yu; Chan, Celia Hoi-Yan
Abstract: STUDY QUESTION: What is the intention to have a second child among women attending outpatient gynecology clinics in three major cities in China? SUMMARY ANSWER: In total, 69.3% of the participants expressed the intention to have a second child and this was related to infertility status, pronatalist attitudes, and sociodemographic factors. WHAT IS KNOWN ALREADY: In 2016, the new universal two-child policy was introduced in China enabling all Chinese couples to have a second child. A government-led national survey revealed that the majority of women included under the policy would be 35 years old and older and thus would be at higher risk of infertility. Previous studies found that fertility intention differs by infertility status. STUDY DESIGN, SIZE, DURATION: A cross-sectional survey was performed to examine the intention of having a second child and its associated factors among infertile and fertile women attending gynecology outpatient clinics in three major cities in China. Clinical nurses approached eligible women in person while waiting for their consultations. Recruitment and data collection were conducted from April to August 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: The survey involved four gynecology outpatient clinics in Beijing, Shenzhen, and Hohhot. Married women aged 20–45 years who were seeking outpatient gynecology care for non-malignant problems were invited to participate. MAIN RESULTS AND THE ROLE OF CHANCE: Data from 974 women were included in the analysis. A total of 69.3% of the women expressed the intention to have a second child, and infertile women were more likely to want a second child compared to fertile women (76.6% vs 61.9%, respectively; P < 0.001). Greater ideal parity facilitated the intention for a second child in both groups, while pronatalist attitudes (meaning that they preferred to have their first childbirth at a younger age and attached greater significance to traditional childbearing beliefs), unexplained infertility, presence of a living child and religious affiliation were associated with greater intention among infertile women. In contrast, in the fertile group, older age, full-time work and lower confidence in achieving parity goals diminished the intention for a second child. Although infertile women displayed greater agreement with pronatalist attitudes and desired a higher ideal parity, they had less confidence in achieving their parity goals than their fertile counterparts. LIMITATIONS REASONS FOR CAUTION: In addition to self-report and self-selection bias, our participants were recruited from urbanized areas and were more educated than the general population. Owing to the extremely busy environment in the clinics, difficulties were encountered in keeping track of the number of women whom the nurses approached, and the response rate was therefore unavailable. WIDER IMPLICATIONS OF THE FINDINGS: With the introduction of the universal two-child policy, there is a need to enhance fertility awareness and to encourage reproductive life planning, as well as to lower the cost of childcare, in order to increase the birth rate in China. Effort is required to make childbearing more compatible with current employment, career and educational development, the burdens of family care (e.g. for elderly parents), social environments and cultural expectations. This is particularly relevant for families who already have a child, as our findings show that their hesitation toward a second child was largely related to difficulties with extra childcare within the woman's current work and family life. STUDY FUNDING/COMPETING INTEREST(s): This study did not receive any funding. The authors declared no competing interests. TRIAL REGISTRATION NUMBER: Not applicable.